Iowa Birdline update, September 18, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for September 18, 1989. Highlights include the sighting of a Black-shouldered Kite and reports from the Iowa Ornithologists' Union fall meeting. Epson - sheet feed/flatbed